A YEAR OF CHANGE. - Clark, Colleen Patrice (Literacy Today (2411-7862))
The article presents an introduction to this issue of the journal that contains articles covering topics including the history behind the transformation of the International Literacy Association (ILA), thoughts from ILA leadership and members alike and computer programming.